β-Arrestin-Mediated Signaling Improves the Efficacy of Therapeutics - Islam A.A.E.-H. Ibrahim; Hitoshi Kurose (Elsevier, 2012)
β-Arrestins (β-arrestin-1 and β-arrestin-2) were first identified as proteins that have the ability to desensitize G protein-coupled receptors (GPCRs). However, it has recently been found that β-arrestins can activate signaling pathways independent of G protein activation. The diversity of these signaling pathways has also been recognized. This leads to an appreciation of β-arrestin-biased agonists, which is a new class of drugs that selectively activate β-arrestin-mediated signaling without G protein activation. In this review, we will discuss the recent advance of β-arrestin-mediated signaling pathways, including a brief account of different biased agonists, their pharmacological applications, and novel β-arrestin research. Keywords:: G protein-coupled receptor, biased agonist, β-arrestin, G protein